A within-person examination of the effect of mentors’ daily ostracism on protégés’ displaced aggression and in-role performance - Li, Miaomiao; Wu, Lunwen; Qin, Yinglin (Frontiers in Psychology, 2023)
Purpose Drawing on social information processing theory and social comparison theory, we test how mentors’ daily ostracism triggers protégés’ envy, thus leading to decreased in-role performance and increased displaced aggression. Design/methodology/approach Using an experience sampling study across three work weeks, the study provided theoretical and empirical examinations of dynamic, within-person processes related to mentors’ ostracism. Findings Mentors’ daily ostracism triggers protégés’ envy, which mediates the effect of mentors’ daily ostracism on protégés’ displaced aggression and in-role performance. Our findings supported our hypothesis of the buffering effect of mentorship quality on the negative effect of mentors’ ostracism on protégés’ envy but did not show a significant moderating effect on the mediating effect of protégés’ emotions between mentors’ daily ostracism and protégés’ behaviors. Research limitations/implications Our study focused on the victims of mentors’ ostracism on a daily basis. We constructed an overarching theoretical model to investigate how, why, and when mentors’ daily ostracism leads to protégés’ emotional and behavioral variability. Practical implications The study provided how to cope with ostracism and envy. Originality/value We discuss the theoretical implications of our findings for research on mentors’ ostracism, protégés’ emotions, and protégés’ behaviors.